Step-by-step design of a LLC resonant converter for EV fast charging applications - Rocha, João (2024)
Electric mobility is already well established in societies, but there are still several technological challenges to overcome. Specifically, a key challenge is the concern about charging systems, which should be faster and more efficient. In this context, regarding the DC-DC back-end power stage, a special emphasis is given to LLC resonant power converters. Aligned with this context, this paper presents a step-by-step design and description of a LLC resonant power converter. MATLAB and PSIM simulation models were developed for validating, respectively, the gain design of the LCC tank and the analysis of the operation considering such different designs. For validation purposes, an input voltage of 900 V, an output voltage of 900 V, and a resonant frequency of 100 kHz were considered. The validating results were obtained for different conditions of operation, according to the different designs, showing a maximum estimated efficiency of 99.5%.